Research on energy-saving method based on reconfigurable network architecture - Sheng-quan LIAO; Chun-ming WU; Bin WANG; ming JIANG (Tongxin xuebao)
With the aim to address the problem that current energy-saving algorithms in the IP network were low practical,an energy-saving method in the reconfigurable network architecture base on its natural features was proposed that the central server unified manages the routing configuration of all the routers.The method firstly using the modified OSPF protocol algorithm to determine a candidate link set in which a l the links were probably closed or sleep,then the mul-ti-commodity model was utilized to remap the traffic volume of these links to other physical paths.Thus,some links can be idle since their data flows had been redirected.It was reasonable to power off idle physical links for the purpose of saving energy.Finally,the simulated experiments had verified the effects of saving energy and the differences between the proposed algorithm and the high recognized energy-saving method –GreenTE were given.